Students’ Perceptions in Implementation Problem-Based Learning (PBL) for Heating, Ventilation and Air Conditioning (HVAC) System Course - Mustafa, Mohd Syafiq; Fatimah Yusof; Ashraf Abdul Rahman; Kamaruzaman Musa; Kamarul Aini Sari; Syamil Ismail; Anis Shazzuani Aziz (Human Sustainability Procedia, 2022)
Problem-based learning (PBL) is recognized as one of the most effective strategies for interactive learning. The technique has the potential to enhance the existing learning paradigm in order to accommodate 21st century learning. This aim of this study is to identify the students’ perception in implementation PBL for HVAC system course. The questionnaire with five question text have been distributed to 16 students that attended for the HVAC system course. The result indicates the positive perception in PBL implementation according to the percentage. PBL can be a good activity in class and align with the student-centered learning.